Surgery of Schwannoma in the upper limb – sensitivity and specificity of preoperative magnetic resonance imaging and relation between tumour size and symptoms - Emanuel Istefan; Johannes Belstock; Lars B. Dahlin; Erika Nyman (BMC Musculoskeletal Disorders, 2023)
Abstract Background Benign peripheral nerve tumours consist of different types, most commonly Schwannomas. Preoperative Magnetic Resonance Imaging (MRI) is commonly performed before surgery and Pathoanatomical Diagnosis (PAD) confirms the diagnosis. Our aims were to study the utility of MRI and the relation between tumour size and symptoms. Methods Retrospectively, patients, surgically treated for benign nerve tumours between 2008 and 2019, were identified and preoperative MRI, with measurement of tumour size, PAD, symptoms, peroperative details, and symptomatic outcomes of surgery, were analysed. Results The sensitivity and specificity to correctly identify Schwannomas with preoperative MRI were 85% and 50%, respectively, based on 30 Schwannomas and nine neurofibromas that were identified. Tumour size did not affect the presence of preoperative symptoms, but patients with sensory dysfunction at last follow-up had larger Schwannomas (p < 0.05). Symptoms as a palpable tumour, paraesthesia and pain improved by surgical excision (p < 0.001, p < 0.001 and p < 0.012, respectively), but sensory and motor dysfunction were common postoperatively. No malignant peripheral nerve sheath tumours (MPNST) were found. Using a surgical microscope, instead of only loop magnification, lowered the risk of perioperative nerve injuries (p < 0.05), but did not further diminish postoperative symptoms. Conclusions Early and accurate diagnosis of Schwannomas is valuable for adequate presurgical preparation and prompt surgical intervention. Preoperative examination with MRI has a high sensitivity, but low specificity; although recent advancement in MRI technology indicates improvement in diagnostic precision. Surgical excision is preferably performed early in conjunction with symptomatic debut to improve outcome.